Quantification of non-transferrin bound iron (NTBI) in human serum by isotope dilution mass spectrometry (IDMS). Issue 10 (2nd August 2019) - Yang, Dongxiao; Ng, Xue Qin; Walczyk, Thomas
Abstract : NTA· 57 Fe is used to capture NTBI and saturate transferrin with iron so that NTBI can be separated through ultrafiltration. Abstract : Non-transferrin bound iron (NTBI) in serum can induce oxidative stress, even when present in minute amounts, due to its ability to catalyze the formation of reactive oxygen species (ROSs). Techniques to accurately quantify NTBI are needed in order to study its nature and possible health effects. To date, no gold standard method for serum NTBI quantification has been established. Existing methods yielded highly divergent results in previous interlaboratory comparisons when compared to each other. Here, we present the development and validation of a novel assay for serum NTBI quantification using isotope dilution mass spectrometry (IDMS) and negative thermal ionization mass spectrometry (NTI-MS) for isotopic analysis. NTBI is not a single species in serum but the fraction of iron not shielded by proteins from chemical reaction. In our assay, an isotopically labelled 57 Fe(iii ) spike chelated by nitrilotriacetic acid (NTA· 57 Fespk ) is mixed with blood during sampling to allow instant capture of NTBI by NTA while vacant binding sites of transferrin are being saturated with the 57 Fe spike. NTBI is separated from the serum by ultrafiltration and quantified using an isotopically enriched 58 Fe spike. Systematic evaluation of iron binding to NTA revealed potential artifacts in previous assays. Iron supplementation (65 mg elemental iron as ferrous fumarate) induced detectable concentrations of NTBI in serum in four out of six apparently healthy, adult males of Asian ethnicity (0.21 ± 0.14 μmol L −1 ; p < 0.05).